Multiple cystic lung disease in a smoker - Amit Panjwani; Mohamed Redha Salman (SpringerOpen, 2022)
Abstract Background Pulmonary cyst is a rounded lung parenchymal lucency, usually containing air or fluid. Approach to establishing the etiology of lung cyst includes determining their location, number, distribution, and presence or absence of associated computed tomography findings (associated with nodules or ground-glass attenuation). Multiple cysts may be seen in various diseases, and radiological imaging is the usual starting point in detecting lung cysts. Importance of adequate clinical examination accompanied with relevant investigations in securing the etiology of lung cysts cannot be overemphasized. We present a first case of a rare multiple cystic lung disease from the Kingdom of Bahrain that was successfully managed with oral corticosteroids. Case presentation A 42-year-old male, chronic smoker presented with progressive dyspnea and productive cough of 1 year duration. He was evaluated and found to have multiple variable sized thin and thick-walled cysts with bizarre shapes in both lungs. A diagnosis of pulmonary Langerhans' cell histiocytosis was made, and the patient was treated with smoking cessation and oral corticosteroids for 9 months. Conclusion Patients with characteristic clinical and radiological features can be diagnosed as pulmonary Langerhans' cell histiocytosis, without a tissue biopsy. A good response may be seen with smoking cessation and oral corticosteroids in selected group of patients.